Identification of chromosomal fusion sites in Arabidopsis mutants using sequential bicolour BAC-FISH - Mokros, Petr; Vrbsky, Jan; Siroky, Jiri (Genome, 2006)
Double stranded chromosomal breaks are repaired by homologous recombination or nonhomologous end joining (NHEJ). When broken chromosome ends are fused together by NHEJ, the resulting dicentric chromosomes can be detected as anaphase bridges during the subsequent mitosis. Telomeres in the absence of functional telomerase shorten, became unprotected, and are eventually recognized by the cell repair system as double stranded breaks. As result, chromosomes of Arabidopsis thaliana plants that are deficient in the gene for telomerase reverse transcriptase (TERT) are prone to chromosome fusions. We use Arabidopsis tert-/- mutants as a model system for analyzing terminal chromosome fusions. Here we report a novel and sensitive cytogenetic assay for the identification and characterization of chromosome-terminal fusion events by employing fluorescence in situ hybridization (FISH) with multiple probes and a repeated hybridization approach. A mixture of chromosome-specific subtelomeric probes is applied successively in 3 FISH reactions to the slides containing mitotic anaphase figures with anaphase bridges. Each figure is registered by a CCD camera after each in situ hybridization procedure. By comparing the signals presented on the bridge in successive images the assessment of the particular chromosome arms involved in fusion is possible. This experimental setup enables unambiguous identification of individual chromosome ends employed in fusion events.
Keywords: zlomy chromozomů; Gene Fusion; Arabidopsis; mutace; Telomerase; Chromosomes, Artificial, Bacterial; rostlinné geny; fúze genů; Chromosome Breakage; chromozomy rostlin; Genes, Plant; telomerasa; Mutation; hybridizace in situ fluorescenční; Chromosomes, Plant; umělé bakteriální chromozomy; In Situ Hybridization, Fluorescence